The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1088/1742-6596/1517/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis simulation of parallel cell in modular battery pack for electric vehicle application

Abstract: Modular design of battery pack for electric vehichle (EV) is an important things to consider. Because in modular battery pack, cost to manufacture can be reduced also easiness in handling. Modular battery pack also meant to be easily swapped between every modules. In this paper were presented the thermal analysis of modular battery pack that generate heat during charging or discharging process. Heat flux generated by the batteries will affect its surrounding thus increase the temperature of the batteries. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The simulation of the conjugate heat transfer has been simplified by employing an equivalent thermal conductivity of cell that consists of various materials. It has been found that the maximum temperature and the temperature deviation of curved duct were lower than those of straight duct.J Raharjo et al [17]investigate the heat power generated by the cells, the effect on surrounding air, and heat generated by the current flow in the circuit. Simulation result were showing that the the thermal behavior of the module battery can be secured under its maximal operating condition.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of the conjugate heat transfer has been simplified by employing an equivalent thermal conductivity of cell that consists of various materials. It has been found that the maximum temperature and the temperature deviation of curved duct were lower than those of straight duct.J Raharjo et al [17]investigate the heat power generated by the cells, the effect on surrounding air, and heat generated by the current flow in the circuit. Simulation result were showing that the the thermal behavior of the module battery can be secured under its maximal operating condition.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have performed thermal analysis for electric vehicle batteries using simulation. For example, Raharjo et al [30] conducted a thermal analysis of modular battery by computational fluid dynamics (CFD) simulation to understand its thermal behavior, prevent overheating, and maintain battery life. Divakaran et al [31] performed finite element simulation to analyze 18,650 lithium-ion batteries' thermal behavior under two conditions: with and without cooling systems.…”
Section: Introductionmentioning
confidence: 99%